Exposure to triptolide affects follicle development in NIH mice: Role of endoplasmic reticulum stress in granulosa cell apoptosis. (January 2017) - Zeng, Y; Sun, H; Li, Y; Shao, M; Han, P; Yu, X; He, L; Xu, Y; Li, S
Triptolide (TPL) is a main active compound isolated from Tripterygium wilfordii Hook f. Despite its positive therapeutic effect, the female reproductive toxicity of TPL is still the bottleneck of clinical application. The study was designed to investigate the adverse effects on mice ovary and underlying mechanism of TPL. Adult female NIH mice were treated with two therapeutic doses of TPL (25 and 50 μg/kg/d) for 50 days, respectively. Mice estrous cycle was detected by vaginal cytology method. Half mice from each group were selected randomly to perform superovulation. Quality and quantity of ovulated eggs were evaluated. Other mice from each group were executed for morphological study. Ovarian histological sections were stained by H&E staining for ovarian pathologic detection and follicular counts. Apoptotic granulosa cell (GC) was detected by terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay. Endoplasmic reticulum (ER) stress-related proteins and antiapoptotic X-linked inhibitor of apoptosis protein (XIAP) were detected by immunohistochemical method. Two doses of TPL resulted in estrous cycle disorder and follicles in development reservoir impairment. Quality and quantity of mice ovulated eggs significantly decreased after TPL treatment. Ovarian pathologic examination revealed TPL-induced TUNEL-positive GCs increase and ER stress–related proteins (78-kDa glucose-regulated protein, p -protein kinase-like endoplasmic reticulum kinase, p-eukaryotic initiation factor 2α, and CCAAT/enhancer binding protein homologous protein) expression upregulation. Meanwhile, the expression of antiapoptosis protein XIAP in mice ovary was obviously inhibited by TPL. Our results may demonstrate that therapeutic doses of TPL can injure ovary function, but there is no difference between high-dose and low-dose groups. GCs apoptosis by ER stress pathway and antiapoptotic function impairment may partly mediate TPL-induced ovary toxicity.